Allogeneic hematopoietic cell transplantation in patients with myelodysplastic syndrome using treosulfan based compared to other reduced‐intensity or myeloablative conditioning regimens. A report of the chronic malignancies working party of the EBMT. (12th September 2021) - Shimoni, Avichai; Robin, Marie; Iacobelli, Simona; Beelen, Dietrich; Mufti, Ghulam J.; Ciceri, Fabio; Bethge, Wolfgang; Volin, Liisa; Blaise, Didier; Ganser, Arnold; Luft, Thomas; Chevallier, Patrice; et al.
Summary: Allogeneic haematopoietic‐cell transplantation (allo‐HCT) is a potentially curative therapy for high‐risk myelodysplastic syndrome (MDS). Reduced‐intensity conditioning (RIC) is usually associated with lower non‐relapse mortality (NRM), higher relapse rate and similar overall‐survival (OS) as myeloablative‐conditioning (MAC). Fludarabine/treosulfan (FT) is a reduced‐toxicity regimen with intense anti‐leukaemia activity and a favourable toxicity profile. We investigated post‐transplant outcomes in 1722 MDS patients following allo‐HCT with FT ( n = 367), RIC ( n = 687) or MAC ( n = 668). FT and RIC recipients were older than MAC recipients, median age 59, 59 and 51 years, respectively ( P < 0·001) but other disease characteristics were similar. The median follow‐up was 64 months (1–171). Five‐year relapse rates were 25% (21–30), 38% (34–42) and 25% (22–29), after FT, RIC and MAC, respectively, ( P < 0·001). NRM was 30% (25–35), 27% (23–30) and 34% (31–38, P = 0·008), respectively. Five‐year OS was 50% (44–55), 43% (38–47), and 43% (39–47), respectively ( P = 0·03). In multivariate analysis, FT was associated with a lower risk of relapse (HR 0·55, P < 0·001) and better OS (HR 0·72, P = 0·01). MAC was associated with higher NRM (HR 1·44, P = 0·001). In conclusion, FT is associated with similar low relapse rates as MAC and similar low NRM as RIC, resulting in improved OS. FT may be the preferred regimen for allo‐HCT in MDS.